Jefte − paradygmat niespełnionego władcy (Sdz 10, 6−12, 7) - Pikor, Wojciech (The Biblical Annals, 2017)
The story about Jephthah is placed in the middle of the Book of Judges (Judges 10:6-12:7). Therefore we recognise in this figure an important link in the quest for the model of a ruler in the period of pre-monarchic Israel. In order to reconstruct the image of Jephthah as a leader the method of narration has been applied. The narrative programme has confirmed that Jephthah, while seeking to find a solution for the crisis of power, became the paradigm of a ruler. In the light of narrative techniques used by the narrator, Jephthah fails as a paradigm, for he loses his daughter and he is seen by the generation of Ephraim as an unfulfilled ruler. There are three reasons at the source of his unfulfilled power: treating power as a means to satisfy one’s ambition; rejecting power as a service on behalf of the good of his subjects; eventually, no roots in the tradition, history, and religion of the fellowship in which is he to govern.